The Effects of Turmeric, Aloe Vera, and Honey as Natural Remedies for Reducing Scar Visibility_ A Pilot Clinical Trial - Nour Hatem; Wiriatul hasanah; Shahd Rashad; Abdelaziz gomaa; Muji iswanty (Lombok Medical Journal, 2026)
Background: Managing scars effectively is often difficult because most clinical treatments are either too expensive or too invasive for many patients. While ingredients like turmeric, honey, and aloe vera have been used in traditional healing for centuries, we still lack enough clinical evidence on how they perform when combined into a single topical remedy. Purpose: This pilot trial was designed to test the safety and effectiveness of a simple, low-cost natural formulation in improving the appearance of both discolored (dyschromic) and raised (hypertrophic) scars. Methods: We followed ten participants with scars aged between 1 and 12 months. For four weeks, they applied a homemade blend of fresh aloe vera, honey, turmeric, lemon juice, and niacinamide twice daily. To ensure our results were objective, we used 3D imaging to measure scar height and tracked changes in pigmentation. We also gathered direct feedback from the participants regarding scar softness and redness. Results: The outcomes were notably positive. After the month-long treatment, 64% of the volunteers saw their scars flatten by at least 20%, with the most significant changes occurring in hypertrophic cases. Furthermore, 72% of the group showed visible lightening of their skin pigment. The formula worked best on acute scars (under six months old). Participants found the mixture easy to use and reported no side effects, other than a temporary yellow stain from the turmeric that faded quickly. Conclusion: Our findings suggest that this natural blend is a practical and affordable way to improve the texture and color of developing scars. While these initial results are promising, we believe larger, randomized trials are needed to standardize the recipe and confirm its long-term benefits.